1997
DOI: 10.1359/jbmr.1997.12.10.1584
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Transforming Growth Factor-β1 Induces Endochondral Bone in the Baboon and Synergizes with Recombinant Osteogenic Protein-1 (Bone Morphogenetic Protein-7) to Initiate Rapid Bone Formation

Abstract: Several members of the bone morphogenetic protein (BMP) and transforming growth factor-␤ (TGF-␤

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
169
2
5

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(181 citation statements)
references
References 46 publications
5
169
2
5
Order By: Relevance
“…TGF␤1 has been shown to stimulate proliferation and collagen synthesis by osteoblasts and osteoblast precursors. [11][12][13] It also may act as a chemotactic agent in recruiting preosteoblasts to the site of bone injury. PDGF also stimulates mitogenesis of osteoblastic precursors.…”
Section: Discussionmentioning
confidence: 99%
“…TGF␤1 has been shown to stimulate proliferation and collagen synthesis by osteoblasts and osteoblast precursors. [11][12][13] It also may act as a chemotactic agent in recruiting preosteoblasts to the site of bone injury. PDGF also stimulates mitogenesis of osteoblastic precursors.…”
Section: Discussionmentioning
confidence: 99%
“…In the cranial periosteum of the rabbit, the amount of BMP-2 could be greatly reduced by combined use with prostaglandin E 1 (118). TGFb attenuated the stimulatory effect of rhBMP-2 in cultures of human bone marrow stromal cells (70), but stimulated OP-1-dependent bone induction in adult baboons in vivo (119).…”
Section: Hormones and Growth Factors Affecting Bmp Activitymentioning
confidence: 99%
“…11 An investigation of the profiles of type of chondroitins produced by hDFs cultured for 7 days showed greatest similarity with DBP for a combination of BMP-2 and TGF-b1 than by either alone. 6 Other investigators showed synergy of differentiation effects with combinations of BMP-2 and TGFb1 23 or of OP-1 and TGF-b1, 24 but did not make comparisons with demineralized bone.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of cDNA and amplification conditions were optimized for each gene product to reflect the exponential phase of amplification. One microliter of the cDNA solution was used in each PCR (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) cycles at 948C for 1 min, 55 or 608C for 1 min, and 728C for 2 min) with human gene specific primers: bigh3/TGFBI and ID3, 10 WNTs, 11 Cbfa1/Runx2 and Col1A1, 18 and SOX9. 19 …”
Section: Cell Cultures In Collagen Scaffoldsmentioning
confidence: 99%